The Influence of Promotion and Service Quality on Visitor Satisfaction at PT Angsamas Ratu Tama (Case Study on the Vesak Event of the Medan City Government 2596 B.E/2025) - Rahmi, Nadhira; Siahaan, Djames (Journal of Economics and Social Sciences (JESS), 2025)
The event industry in Indonesia is growing rapid growth, especially in organizing cultural and religious-based events that carry strong spiritual and social values. One notable example is the Waisak Celebration 2596 B.E./2025 organized by the Medan City Government in collaboration with PT Angsamas Ratu Tama. This event not only symbolizes interfaith harmony but also contributes to local tourism and economic development. The success of such events depends not only on the number of visitors but also on the effectiveness of promotional strategies and the quality of services provided. This study aims to analyze the influence of promotion and service quality on visitor satisfaction, both partially and simultaneously, as well as to identify which variable has the most dominant effect. The research uses a quantitative approach with multiple linear regression analysis. Data were collected through a questionnaire distributed to 100 respondents who attended the Waisak 2596 B.E./2025 event at Lapangan Benteng, Medan. The results show that both promotion and service quality have a positive and significant effect on visitor satisfaction. Therefore, promotional strategies and service quality play a critical role in enhancing visitor satisfaction during large-scale religious events. These findings are expected to serve as practical references for event organizers in designing more effective promotional and service strategies. Furthermore, this study contributes academically to the development of event management research, particularly within the context of cultural and religious event.